2018
DOI: 10.1016/j.solener.2018.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Sky view factor as predictor of solar availability on building façades

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(28 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…The visible sky factor method is also often used to determine the availability of direct sunlight (Johnson and Watson, 1987;Grimmond et al, 2001;Chatzipoulka et al, 2018). On physical models of urban structures, the shadows and the availability of direct sunlight can be clearly monitored using heliodons.…”
Section: Tools Of Right Of Access To Sunlightmentioning
confidence: 99%
“…The visible sky factor method is also often used to determine the availability of direct sunlight (Johnson and Watson, 1987;Grimmond et al, 2001;Chatzipoulka et al, 2018). On physical models of urban structures, the shadows and the availability of direct sunlight can be clearly monitored using heliodons.…”
Section: Tools Of Right Of Access To Sunlightmentioning
confidence: 99%
“…For a horizontal unobstructed surface, the SVF value is 1, whereas, for a vertical unobstructed façade, it is 0.5. A recent study has shown that SVF can serve to assess the average annual solar irradiance received by building façades [1]. Furthermore, SVF affects the long wave infrared exchanges between the urban fabric and the sky, and thus, it can be also used as indicator of the urban heat island effect.…”
Section: Performance Indicatorsmentioning
confidence: 99%
“…Many studies have shown that, in a city, areas with lower SVF values usually have lower daytime temperatures, which is because they harvest smaller amounts of solar radiation during the daytime [36,37,38,39,40]. Chatzipoulka also showed a significant linear relationship ( R 2 > 0.8) between SVF and annual global irradiance in all orientations, and the strong impact of the solar altitude angle on the relation between SVF and the amount of solar radiation obtained [41]. Ahmadi found that the SVF value imposes a limited effect on outdoor air temperature in summer, while it greatly affects the T g (globe temperature) [42].…”
Section: Introductionmentioning
confidence: 99%